Assistive Technology and Supplementary Treatment for Individuals with Rett Syndrome - Meir Lotan (The Scientific World Journal)
Rett syndrome (RS) is a neurological disorder, affecting mainly females, caused by MECP2 mutations usually resulting in severe physical disability. Due to the physical challenges faced by the individual with RS and her family, her rehabilitation program should support her throughout different daily activities, contexts, and surroundings. Rehabilitation interventions to reverse physical impairments include exercise of various types and different physical modalities. Nevertheless, in the vast majority of cases, hands-on therapeutic intervention opportunities are available for the client through a minute part of her waking hours. Hence, a supplementary system is required in order to engulf the child with a comprehensive network of support. Supplementary intervention can support physical impairment by introducing adaptive techniques, environmental modifications, and assistive technologies. The therapy program of an individual with RS should include the use of assistive technology when such devices improve the user's performance. The term “supplementary management” relates to the fact that this intervention may be performed by nonprofessionals with the supervision of a qualified therapist. Such an intervention can further support the therapeutic goals of the child, at a time when direct intervention is not supplied. The present article will review the available literature on the topic of assistive technology, incorporating the clinical knowledge of the author in the field of RS.